High Prevalence of Tuberculosis Infection and Disease in Child Household Contacts of Adults With Rifampin-resistant Tuberculosis. Issue 5 (8th April 2022) - Kim, Soyeon; Wu, Xingye; Hughes, Michael D.; Upton, Caryn; Narunsky, Kim; Mendoza-Ticona, Alberto; Khajenoori, Saltnat; Gonzales, Pedro; Badal-Faesen, Sharlaa; Shenje, Justin; Omoz-Oarhe, Ayotunde; Rouzier, Vanessa; et al.
Abstract : Background: Household contact (HHC) investigation is an important strategy to identify individuals with tuberculosis (TB) exposure, infection and disease, including those who may benefit from tuberculosis preventive therapy (TPT). Data in children exposed to rifampin-resistant TB are limited. Methods: In preparation for and to inform the feasibility of an interventional trial, HHC of adults with pulmonary rifampin-resistant TB from high TB-burden countries were evaluated in a cross-sectional study. Using interferon-gamma release assay and study-specific and 2015 international consensus definitions of intrathoracic TB in children, we evaluated the prevalence and predictors of TB infection and disease in child (<15 years) HHCs. Results: Of 303 child HHCs, median age (range) 7 years (0−14), 57% [95% confidence interval (CI): 50%–64%] had a positive interferon-gamma release assay result (TB infected). TB infection was associated with the index case smoking ( P = 0.034), being the parent or sleeping in the same room ( P = 0.002) and the child HHC being age ≥5 years and having attended school ( P = 0.013). Four had study-defined confirmed TB and 9 had probable TB, a prevalence of 4.3% (95% CI: 2.6%−7.1%). Using the international consensus definitions, 4 had confirmed TB and 49 had unconfirmed TB, a prevalence of 17.2% (95% CI: 12.9%–22.4%). Twenty (7%) children had received TPT. Conclusions: The prevalence of TB infection and disease was high in child HHC exposed to rifampin-resistant TB. Few children had routinely received TPT. High-quality evidence is needed to inform strong recommendations for and access to TPT in children exposed to TB resistant to rifampin.